Problems of overseas ventures for Singapore construction SMEs - Wong, Yun Tau (2008)
Owing to its small domestic market and lukewarm construction demand, Singapore contractors are increasingly forced to seek their opportunity for growth and revenue in overseas markets. These push factors are further complemented with the strong pull factors in the regions where most of the developing countries are achieving strong growth and offering attractive investment schemes for foreign investments. However, not many Singapore contractors, especially the construction SMEs, were successful in overseas construction. Very little attention was focused on their problems in construction export and the reasons for their failures. As a result, this research was initiated to fill the literature gap. The main objective of this research is to identify the problems of Singapore contractors in overseas ventures and with hindsight formulate the essential framework to assist Singapore contractors to succeed overseas. In order to gain the in-depth understanding of Singapore contractors’ performance overseas, both the case-study approach and survey questionnaire were adopted. The major problems and critical success factors were successfully determined from qualitative analysis. The result of qualitative analysis determined three major problems in the entry stage and one major problem in the operational stage. Out of these four problems, the most critical problem which impeded the respondents’ firms from successfully exporting construction is their smallness in size and limited resources.A final model incorporating the critical success factors across the three different stages in overseas construction ventures and the strategy for growth was formulated after triangulating the research findings with the experiences of SMEs from other industries. Last but not least, this study proposed six solutions to improve construction export condition in which the government is deemed to play a vital role in the success of their implementation.